Two-dimensional / three-dimensional composite perovskite solar cell and preparation method thereof

By designing a two-dimensional perovskite layer and doped nanostructure on rough surfaces in two-dimensional/three-dimensional composite perovskite solar cells, the quantum bound domain effect and stability problems are solved, the light absorption and charge transfer efficiency are improved, and the The device's environmental tolerance and stability.

CN119255624APending Publication Date: 2025-01-03YUNNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411590934.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The quantum bound domain effect of two-dimensional perovskite solar cells leads to an increase in band gap, which reduces the material's absorption efficiency on long-wave light, limits the carrier transmission path, affects the photoelectric conversion efficiency, and three-dimensional perovskite materials are easily affected by The influence of moisture and oxygen leads to poor long-term stability.

Method used

Design a two-dimensional/three-dimensional composite perovskite solar cell structure, including transparent conductive layer, electron transport layer, three-dimensional perovskite layer, two-dimensional perovskite layer, hole transport layer and back electrode layer, the two-dimensional perovskite layer has Rough surfaces and doped with nanostructures such as titanium dioxide nanoparticles or carbon nanotubes in their precursor solutions, form films by spin coating and annealing, adjusting the thickness and surface roughness of the film to reduce the quantum confined domain effect and increase loading Flower motion freedom.

Benefits of technology

Adjust the energy band structure through local thickness changes, improve light absorption performance and charge separation efficiency, reduce carrier recombination, improve photoelectric conversion performance, and enhance the environmental tolerance and stability of the device through nanostructures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255624A_ABST
    Figure CN119255624A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite solar cells, and particularly relates to a two-dimensional / three-dimensional composite perovskite solar cell and a preparation method thereof. The composite perovskite solar cell comprises a transparent conductive layer, an electron transport layer, a three-dimensional perovskite layer, a two-dimensional perovskite layer, a hole transport layer and a back electrode layer which are arranged in sequence, wherein the two-dimensional perovskite layer has a rough surface. In the invention, local thickness change caused by the rough surface of the two-dimensional perovskite layer leads to adjustment of an energy band structure, and a thicker area has a narrower band gap, so that the material can absorb more long-wave light, and the light absorption performance is improved. Besides, according to the surface roughness of the two-dimensional perovskite layer, by increasing the local thickness, the motion freedom degree of current carriers is increased, the current carriers can move more freely in areas with different thicknesses, then the charge transmission and separation efficiency is improved, charge recombination is reduced, and the overall photoelectric conversion performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells, and specifically relates to a two-dimensional / three-dimensional composite perovskite solar cell and a preparation method thereof. Background Art

[0002] Two-dimensional perovskite materials have a layered structure, usually composed of alternating organic cations and inorganic perovskite layers. The layered structure of two-dimensional perovskite materials makes them more resistant to environmental factors such as humidity and oxygen. Compared with three-dimensional perovskite materials, two-dimensional perovskites exhibit higher moisture resistance, heat resistance and light stability, which can effectively extend the service life of the device (Progress and challenges in layered two-dimensional hybrid perovskites, Nanotechnology, Vol. 33, pp.292501, 2022). Although two-dimensional perovskite materials have advantages in stability and defect passivation, the efficiency of solar cells made using two-dimensional perovskite materials alone is currently difficult to compare with the efficiency of cells obtained based on three-dimensional perovskites.

[0003] Combining two-dimensional perovskite materials with three-dimensional perovskite materials to form two-dimensional / three-dimensional composite perovskite solar cells can simultaneously utilize the advantages of both types of materials, further improving the performance of solar cells. On the one hand, three-dimensional perovskite materials have broad light absorption characteristics and high carrier mobility, while two-dimensional perovskite materials have strong interface passivation. Combining two-dimensional materials with three-dimensional materials can effectively improve the charge separation efficiency of the interface, reduce the recombination loss of carriers, and thus improve the photoelectric conversion efficiency. On the other hand, three-dimensional perovskite materials are more susceptible to moisture and oxygen, resulting in poor long-term stability. By introducing two-dimensional materials, a "protective layer" can be formed on the surface to enhance the environmental tolerance of the overall device, especially showing higher stability under humid conditions (Deterministic fabrication of 3D / 2D perovskite bilayer stacks for durable and efficient solar cells, Science, Vol 377, pp.1425, 2022; Advances in mixed 2D and 3D perovskite heterostructure solar cells: A comprehensive review, Nano Energy, Vol.118,pp. 108979, 2023).

[0004] Although two-dimensional / three-dimensional composite perovskite solar cells have made some progress in improving the stability and photoelectric performance of cells by combining two-dimensional and three-dimensional perovskite materials, the quantum confinement effect of the two-dimensional perovskite layer has hindered the further improvement of its performance. On the one hand, the quantum confinement effect leads to an increase in the band gap, which reduces the material's absorption efficiency of long-wave light and reduces the photoelectric conversion efficiency; on the other hand, the quantum confinement effect limits the carrier transmission path, resulting in a decrease in carrier mobility and an increase in the recombination rate of charges in the two-dimensional perovskite layer. These factors will reduce the short-circuit current of the solar cell and affect the photoelectric conversion efficiency of the device. Summary of the invention

[0005] To solve the above problems, the present invention provides a two-dimensional / three-dimensional composite perovskite solar cell structure, comprising a transparent conductive layer, an electron transport layer, a three-dimensional perovskite layer, a two-dimensional perovskite layer, a hole transport layer, and a back electrode layer arranged in sequence; wherein the two-dimensional perovskite layer has a rough surface.

[0006] The quantum confinement effect mainly occurs in extremely thin materials. When the thickness of the material drops to near the nanoscale, the movement of electrons and holes is restricted to a specific direction, resulting in energy level splitting and increased band gap, which in turn affects light absorption and carrier transport. The rough surface of two-dimensional perovskites leads to uneven local thickness, with some areas thicker than others. Areas with increased thickness reduce restrictions on electron-hole movement, so this thickness change weakens the quantum confinement effect in local areas, the band gap becomes smaller, and the intensity of the quantum confinement effect is reduced.

[0007] Furthermore, the 2D perovskite layer contains nanostructures.

[0008] Furthermore, the nanostructure is titanium dioxide nanoparticles or zinc oxide nanoparticles or carbon nanotubes.

[0009] Furthermore, the weight ratio of the nanostructure to the perovskite material in the two-dimensional perovskite layer is 1%-5%. An appropriate amount of nanostructure can effectively enhance light scattering, increase light absorption, and improve charge separation efficiency. However, if there are too many nanostructures, it will affect the normal growth of perovskite crystals, reduce the migration efficiency of carriers, and cause the recombination rate to increase, thereby affecting the photoelectric conversion efficiency.

[0010] Furthermore, the average surface roughness of the two-dimensional perovskite layer is 5-20 nanometers. The thickness of the general two-dimensional perovskite layer is 20-100 nanometers. This thickness design combined with the moderate surface roughness is conducive to optimizing the optoelectronic performance and device stability.

[0011] On the other hand, the present invention provides a method for preparing a two-dimensional / three-dimensional composite perovskite solar cell, comprising the following steps: Step 1: preparing a transparent conductive layer; Step 2, preparing an electron transport layer on the transparent conductive layer; Step 3, preparing a three-dimensional perovskite layer on the electron transport layer; Step 4, spin-coating the two-dimensional perovskite layer precursor solution onto the three-dimensional perovskite layer to prepare a two-dimensional perovskite layer on the three-dimensional perovskite layer; Step 5, preparing a hole transport layer on the two-dimensional perovskite layer; Step 6: preparing a back electrode layer on the hole transport layer; Wherein, in step 4, nanostructures are doped into a precursor solution of the two-dimensional perovskite layer.

[0012] When nanostructures are doped in the precursor solution, these nanostructures act as physical barriers during solution coating and film formation, interfering with the growth process of perovskite grains. Due to the presence of nanostructures, the perovskite material cannot be uniformly deposited and crystallized in all areas during formation, resulting in local accumulation or defects in the perovskite layer around the nanostructures. This uneven formation process causes the two-dimensional perovskite layer to form a rough surface. In addition, the doping of nanostructures also affects the growth dynamics of perovskite crystals. For example, the nanostructures provide additional nuclei in different regions of the two-dimensional perovskite layer, promoting the rapid growth of local grains. These uneven grain growths lead to inconsistent grain size and morphology on the film surface, thereby forming a rough surface.

[0013] Furthermore, the nanostructure is titanium dioxide nanoparticles or zinc oxide nanoparticles or carbon nanotubes.

[0014] Furthermore, in step 4, the nanostructure is doped in the precursor solution of the two-dimensional perovskite layer by ultrasonic dispersion.

[0015] Furthermore, in step 4, the weight ratio of the nanostructure to the perovskite material in the two-dimensional perovskite layer is 1%-5%.

[0016] Furthermore, in step 4, after the two-dimensional perovskite layer precursor solution is spin-coated onto the three-dimensional perovskite layer, the two-dimensional perovskite layer is annealed at a temperature of 60-80°C. This annealing temperature is lower than the annealing temperature when the two-dimensional perovskite layer is normally prepared. On the one hand, the nanostructure affects the crystallization dynamics of the perovskite, plays the role of a crystal nucleus, and promotes the local crystallization of the perovskite. Based on this, the crystallization of the perovskite film can be carried out at a relatively low temperature; on the other hand, annealing at a lower temperature can alleviate the local stress caused by the nanostructure during the crystallization of the film, avoid excessive grain growth and local defects, and thus help maintain the uniformity and surface morphology of the film.

[0017] Beneficial effects of the present invention: (1) The local thickness variation caused by the rough surface of the two-dimensional perovskite layer leads to the adjustment of the band structure. The thicker area will have a narrower band gap, which enables the material to absorb more long-wavelength light and improves the light absorption performance.

[0018] (2) The surface roughness of the two-dimensional perovskite layer increases the freedom of carrier movement by increasing the local thickness. Carriers can move more freely in regions of different thicknesses, improving the charge transfer and separation efficiency, reducing charge recombination, and improving the overall photoelectric conversion performance.

[0019] (3) The annealing process of the two-dimensional perovskite layer can be carried out at a relatively low temperature, which avoids the decomposition or damage of the organic part of the two-dimensional perovskite material, ensures the stability of the perovskite phase structure, and inhibits denaturation or aggregation at high temperature.

[0020] Based on the above beneficial effects, the present invention has good application prospects in the field of perovskite solar cell technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of a two-dimensional / three-dimensional composite perovskite solar cell.

[0022] In the figure: 1. Transparent conductive layer; 2. Electron transport layer; 3. Three-dimensional perovskite layer; 4. Two-dimensional perovskite layer; 5. Hole transport layer; 6. Back electrode layer; 41. Nanostructure. DETAILED DESCRIPTION

[0023] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below with reference to the accompanying drawings and examples.

[0024] Example 1 The present invention provides a two-dimensional / three-dimensional composite perovskite solar cell, such as Figure 1As shown, it includes a transparent conductive layer 1, an electron transport layer 2, a three-dimensional perovskite layer 3, a two-dimensional perovskite layer 4, a hole transport layer 5, and a back electrode layer 6, which are arranged in sequence. The transparent conductive layer 1 is indium tin oxide (ITO), and the thickness of the transparent conductive layer 1 is 100-150 nanometers; the material of the electron transport layer 2 (ETL) is tin dioxide or PCBM, and the thickness of the electron transport layer 2 is 20-40 nanometers; the three-dimensional perovskite layer 3 is methylamine lead iodine (MAPbI3), and the thickness of the three-dimensional perovskite layer 3 is 200-400 nanometers to ensure efficient absorption of visible light. The three-dimensional perovskite layer 3 has good photoelectric properties and can generate efficient electron-hole pairs; the two-dimensional perovskite layer 4 is (PEA)2PbI4, and the thickness of the two-dimensional perovskite layer 4 is between 10-50 nanometers. The hole transport layer 5 (HTL) is Spiro-OMeTAD, and the thickness of the hole transport layer 5 is 100-200 nanometers, which is used to conduct holes and block electrons from entering the back electrode layer 6. The back electrode layer 6 is silver, gold, copper or aluminum, and the thickness is 50-100 nanometers. Among them, the two-dimensional perovskite layer 4 contains a nanostructure 41, and the nanostructure 41 is titanium dioxide nanoparticles or zinc oxide nanoparticles or carbon nanotubes. Preferably, the nanostructure 41 is titanium dioxide nanoparticles. Titanium dioxide has good electronic conductivity and can improve the carrier transmission efficiency in the two-dimensional perovskite layer 4. In addition, titanium dioxide nanoparticles have good chemical and thermal stability, can passivate the surface defects of the three-dimensional perovskite layer 3, and improve the long-term stability of the battery. The weight ratio of the nanostructure 41 to the perovskite material in the two-dimensional perovskite layer 4 is 1%-5%. The two-dimensional perovskite layer 4 has a rough surface. The average surface roughness of the two-dimensional perovskite layer 4 is 5-20 nanometers, and this roughness range helps to enhance the scattering and reflection effects of light, prolong the path of light in the two-dimensional perovskite layer 4, and thus improve the light absorption efficiency. In addition, the rough surface is also conducive to improving the interface bonding between the hole transport layer 5 and the two-dimensional perovskite layer 4, improving the charge transfer efficiency and reducing charge recombination.

[0025] Example 2 The present invention provides a method for preparing a two-dimensional / three-dimensional composite perovskite solar cell, which mainly includes six steps. In order to clearly illustrate the present invention, this embodiment takes a MAPbI3 / (PEA)2PbI4 composite perovskite solar cell as an example, and the six steps are respectively described as follows: Step 1: Prepare a transparent conductive layer.

[0026] In this step, ITO is selected as the transparent conductive layer 1 with a thickness of 100-150 nanometers. After being cleaned, the transparent conductive layer 1 is surface treated in oxygen plasma to improve the cleanliness and wettability of the transparent conductive layer 1 .

[0027] Step 2: preparing an electron transport layer on the transparent conductive layer.

[0028] In this step, 30 ml of deionized water is measured in a 50 ml beaker with a measuring cylinder, and a magnetic bar is added for stirring. 1.015 g SnCl2.2H2O tin (II) chloride dihydrate and 0.335 g thiourea are added in sequence, and stirred at room temperature for 36 h to obtain a clear yellow solution. The solution is then centrifuged (9000 rppm, 5 min), the supernatant is taken after centrifugation, and then filtered with a 0.22 micron PTFE filter membrane. The filtrate is the SnO2 precursor. The precursor is then added dropwise to the ITO substrate, and the spin coating speed is set to 2000 rpm for 30 seconds to prepare a uniform tin dioxide film with a thickness of 20-40 nanometers; the spin-coated tin dioxide film is then placed on a heating table at 200 ° C for annealing for 30-60 minutes to form a dense electron transport layer 2.

[0029] Step 3: Prepare a three-dimensional perovskite layer on the electron transport layer.

[0030] In this step, methylamine iodide (MAI) and lead iodide (PbI2) are dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a molar ratio of 1:1, with a solution concentration of about 1.3 M, and stirred until completely dissolved; then the MAPbI3 precursor solution is dropped on the electron transport layer 2, and the spin coating speed is 2000 rpm for 30 seconds to form a uniform film with a thickness of 200-400 nm; then the substrate is annealed on a hot plate at 100 °C for 10 minutes to ensure that the MAPbI3 layer is well crystallized.

[0031] Step 4: spin-coat the two-dimensional perovskite layer precursor solution onto the three-dimensional perovskite layer to prepare a two-dimensional perovskite layer on the three-dimensional perovskite layer.

[0032] In this step, phenylethylamine (PEA) and lead iodide (PbI2) are dissolved in a DMF solvent at a molar ratio of 2:1 to form a (PEA)2PbI4 precursor solution; titanium dioxide nanoparticles are then added to the two-dimensional perovskite precursor solution, and the weight ratio of the nanoparticles is preferably controlled at 1%-5% of the perovskite material. To ensure uniform dispersion of the nanoparticles, ultrasonic treatment can be performed for 10-15 minutes after addition; then the (PEA)2PbI4 solution doped with nanostructures is dropped onto the three-dimensional perovskite layer 3 (MAPbI3 layer) at a spin coating speed of 1500 rpm for 30 seconds to form a two-dimensional perovskite layer 4 with a thickness of 10-50 nanometers; finally, annealing is performed at a temperature of 60-80 °C for 10 minutes to ensure the formation of the (PEA)2PbI4 crystal structure and stabilize the distribution of the nanostructures. Preferably, a distributed deposition method is used to prepare the two-dimensional perovskite layer 4: first, a thinner two-dimensional perovskite layer 4 is prepared, and then a small amount of titanium dioxide nanoparticles are spin-coated on the layer, and finally a layer of two-dimensional perovskite material is set, so that the titanium dioxide nanoparticles can be evenly distributed inside the two-dimensional perovskite layer 4, and the charge transfer between the three-dimensional and two-dimensional layers is enhanced. In addition, a gradient doping method is used to enhance the synergy between the two-dimensional perovskite layer 4 and the three-dimensional perovskite layer 3: the content of titanium dioxide nanoparticles is increased in the area close to the three-dimensional perovskite layer 3, so as to enhance the electron transfer efficiency at the interface, and the content of titanium dioxide nanoparticles is reduced in the area away from the interface, thereby ensuring the integrity of the crystal structure. For the annealing process, in the early stage of the formation of the two-dimensional perovskite layer 4, a lower temperature annealing (such as 60-70 ° C) is used to make the perovskite crystal grow well, while avoiding the agglomeration of nanoparticles or causing excessive crystal growth, thereby maintaining the effective synergy between the two-dimensional perovskite layer 4 and the three-dimensional perovskite layer 3. At the later stage of the formation of the two-dimensional perovskite layer 4, a higher temperature annealing (e.g., 70-80 °C) is used.

[0033] Step 5: Prepare a hole transport layer on the two-dimensional perovskite layer.

[0034] In this step, Spiro-OMeTAD is dissolved in chlorobenzene at a concentration of 72 mg / mL, and additives such as lithium bistrifluoromethanesulfonimide (Li-TFSI, 170 mg / mL) and 4-tert-Butylpyridine (tBP, 30 μL) are added and stirred evenly; the precursor solution is then spin-coated on the two-dimensional perovskite layer at a spin coating speed of 3000 rpm for 30 seconds to form a hole transport layer 5 with a thickness of 100-200 nanometers; the substrate is then placed in an air environment to allow Spiro-OMeTAD to slowly oxidize in the air, usually for 12 hours to ensure the formation of a stable hole transport layer 5.

[0035] Step 6: Prepare a back electrode layer on the hole transport layer.

[0036] In this step, the back electrode material is deposited on the hole transport layer 5 by thermal evaporation or sputtering. The thickness of the back electrode layer 6 is 50-100 nanometers.

[0037] In step 4, further, the nanostructure 41 includes titanium dioxide nanoparticles and carbon nanotubes. That is to say, the nanostructure 41 is a combination of two materials. Carbon nanotubes have extremely high electrical conductivity, which can significantly improve the overall electrical conductivity of the perovskite layer, improve the charge transfer path, especially between the two-dimensional perovskite layer 4 and the three-dimensional perovskite layer 3, and enhance the interlayer synergistic effect. In addition, carbon nanotubes can also enhance the mechanical strength and light absorption capacity of the film. Titanium dioxide nanoparticles and carbon nanotubes are combined. Titanium dioxide nanoparticles mainly play a role in improving electron transmission, while carbon nanotubes have excellent electrical conductivity and can improve the overall carrier transmission path. In this way, while changing the quantum confinement effect of the two-dimensional perovskite layer 4, it is also possible to achieve a balance between electron and hole transmission during charge separation and transmission, reduce charge recombination, and improve photoelectric conversion efficiency.

[0038] In summary, the present invention provides a two-dimensional / three-dimensional composite perovskite solar cell and a preparation method thereof. The composite perovskite solar cell comprises a transparent conductive layer 1, an electron transport layer 2, a three-dimensional perovskite layer 3, a two-dimensional perovskite layer 4, a hole transport layer 5, and a back electrode layer 6 arranged in sequence; wherein the two-dimensional perovskite layer 4 has a rough surface. In the present invention, the local thickness change caused by the rough surface of the two-dimensional perovskite layer 4 leads to the adjustment of the band structure, and the thicker area will have a narrower energy gap, so that the material can absorb more long-wavelength light and improve the light absorption performance. In addition, the surface roughness of the two-dimensional perovskite layer 4 increases the freedom of movement of carriers by increasing the local thickness, and the carriers can move more freely in different thickness areas, which improves the charge transfer and separation efficiency, reduces charge recombination, and improves the overall photoelectric conversion performance.

[0039] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A two-dimensional / three-dimensional composite perovskite solar cell, comprising a transparent conductive layer, an electron transport layer, a three-dimensional perovskite layer, a two-dimensional perovskite layer, a hole transport layer, and a back electrode layer arranged in sequence; characterized in that: The two-dimensional perovskite layer has a rough surface.

2. The two-dimensional / three-dimensional composite perovskite solar cell according to claim 1, characterized in that: The two-dimensional perovskite layer contains nanostructures.

3. The two-dimensional / three-dimensional composite perovskite solar cell according to claim 2, characterized in that: The nanostructure is titanium dioxide nanoparticles or zinc oxide nanoparticles or carbon nanotubes.

4. The two-dimensional / three-dimensional composite perovskite solar cell according to claim 3, characterized in that: The weight ratio of the nanostructure to the perovskite material in the two-dimensional perovskite layer is 1%-5%.

5. The two-dimensional / three-dimensional composite perovskite solar cell according to claim 1, characterized in that: The average surface roughness of the two-dimensional perovskite layer is 5-20 nanometers.

6. A method for preparing a two-dimensional / three-dimensional composite perovskite solar cell, comprising the following steps: Step 1: preparing a transparent conductive layer; Step 2, preparing an electron transport layer on the transparent conductive layer; Step 3, preparing a three-dimensional perovskite layer on the electron transport layer; Step 4, spin-coating the two-dimensional perovskite layer precursor solution onto the three-dimensional perovskite layer to prepare a two-dimensional perovskite layer on the three-dimensional perovskite layer; Step 5, preparing a hole transport layer on the two-dimensional perovskite layer; Step 6: preparing a back electrode layer on the hole transport layer; The method is characterized in that: in step 4, nanostructures are doped into a precursor solution of the two-dimensional perovskite layer.

7. The method for preparing a two-dimensional / three-dimensional composite perovskite solar cell according to claim 6, characterized in that: The nanostructure is titanium dioxide nanoparticles or zinc oxide nanoparticles or carbon nanotubes.

8. The method for preparing a two-dimensional / three-dimensional composite perovskite solar cell according to claim 7, characterized in that: In step 4, the nanostructure is doped in a precursor solution of a two-dimensional perovskite layer by ultrasonic dispersion.

9. The method for preparing a two-dimensional / three-dimensional composite perovskite solar cell according to claim 8, characterized in that: In step 4, the weight ratio of the nanostructure to the perovskite material in the two-dimensional perovskite layer is 1%-5%.

10. The method for preparing a two-dimensional / three-dimensional composite perovskite solar cell according to claim 9, characterized in that: In step 4, the two-dimensional perovskite layer precursor solution is spin-coated onto the three-dimensional perovskite layer and then annealed.